Spatial Features of L‐Band Equinoctial Scintillations From Equator to Low Midlatitude at Around 95°E During 2015–2016. Issue 9 (15th September 2018) - Dutta, Barsha; Kalita, Bitap Raj; Bhuyan, P. K.; Sharma, S.; Tiwari, R. C.; Wang, K.; Hozumi, K.; Tsugawa, T.; Yokoyama, T.; Le Huy, M.; Pham, T. T. H.
Abstract: The nature and extent of the irregularities causing L‐band nighttime scintillations at a group of five stations Dibrugarh (27.5°N, 95°E, 43° dip), Kohima (25.6°N, 94.1°E, 39° dip), Aizawl (23.7°N, 92.8°E, 36° dip), Port Blair (11.6°N, 92.7°E, 9° dip), and Cocos Islands (12.2°S, 96.8°E, 43° dip) from the northern low midlatitudes to southern midlatitudes along 95°E meridian is investigated. Global Navigation Satellite System/Global Positioning System/ionosonde measurements during the equinoctial months of 2015–2016 have been utilized. The northernmost station Dibrugarh and the southernmost station Cocos Islands are magnetically conjugate. Scintillations occur more frequently around the equatorial ionization anomaly crest where the background charge density (total electron content crest‐to‐trough ratio) plays an important role. It is also observed that L‐band scintillations around this sector decrease considerably from equinoctial months of 2015 to equinoctial months of 2016. The anomalous El Niño‐Southern Oscillation and quasi‐biennial oscillation recorded during the 2015–2016 winter might have contributed partly to the suppression of irregularities (and hence scintillations) in the succeeding equinox. Strong pre‐midnight scintillations when triggered by equatorial spread F occur simultaneously at all stations. The zonal/vertical drift velocities of irregularities estimated from the time delay of occurrence of scintillations decrease from postsunset to midnight hours. On the other hand, simultaneous sporadic E and post‐midnight scintillations occur over Dibrugarh and Cocos Islands in the absence of scintillations at the equator. Azimuthal position of post‐midnight scintillations at these two locations suggests that they are the manifestation of a frontal structure of sporadic E . Key Points: Strong pre‐midnight scintillations triggered by equatorial spread F are detected from northern to southern midlatitudes Post‐midnight scintillations are triggered by sporadic E at magnetically conjugate midlatitude stations in the absence of equatorial spread F The zonal and vertical drift velocities of irregularities decrease from postsunset to midnight hours